Marzec 1968-1985 [koperta ze znaczkiem] . March 1968-1985. Envelope with stamp (Polska, 1985)
Envelope with brown print on white paper and stamp with red print on white paper without perforation. Envelope, issued in commemoration of the student protest in March 1968. The print on the envelope represents the student march passing through the main gate of Warsaw University. The stamp represents a banner with Solidarity logotype fastened to a cross, with price at 50 zł.